Chapter 2 SHAPING ORGANIZATIONAL CLIMATES TO DEVELOP AND LEVERAGE WORKFORCE NEURODIVERSITY - Volpone, Sabrina (Taylor & Francis, 2022)
Chapter 2 explores how organizations can bolster their workplace inclusion in ways that consider the natural variation in human neurocognitive functioning to provide altered workplace environments that leverage the strengths of all employees. Entitled Shaping Organizational Climates to Develop and Leverage Workforce Neurodiversity, by Sabrina Volpone, Derek Avery, and Julie Wayne, the authors ask why "instead of placing the unnecessary burden on neurodivergent individuals, what if workplaces altered their environments so that all employees - including those who are neurodivergent- could easily apply their strengths at work?" Throughout the chapter, the authors discuss how neurotypical norms have dominated human resource management practices for so long that there is a crucial need to critically analyze these norms and establish new norms if we are going to be able to support neurodivergent applicants and employees. The response offered by these authors is to closely examine all facets of the employment process in light of the role of climate in considering neurodiversity in the workplace. This is accomplished by an initial discussion of the role of psychological climates and their role in supporting neurodiversity in organizations.